University Curriculum and its Role in Preparing for the Teaching Profession and Professional Motivation - Jerad Yousif , Ali (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to identify the role of university curriculum in preparing for the teaching profession with its aspects (specialized-educational and psycho-cultural). It also examines its role in the professional motivation among students at the University of Kufa's College of Education for Girls, according to two variables: major (pure-social-human sciences) and type of study (morning-evening). Two scales were built according to the fundamental scientific procedures and in light of the appropriate statistical means to conclude the results. The results are that the curriculum plays a significant role in preparing for teaching with its specialized and cultural sides and a distinct improvement in the educational and psychological aspects. Moreover, it has a distinctive role in professional motivation. However, there are no significant statistical differences for the research variables except for the bilateral interaction between the two variables of major and type of study for the scale of preparation for the teaching profession in favor of human evening study. The research concluded with a set of recommendations and suggestions.